Open Reviewers Africa - Munene, Aurelia; Ngugi, Wangari Joyce; Owango, Joy; Obanda, Johanssen; Havemann, Johanna; Saderi, Daniela; Korzec, Kornelia (My University, 2021)
Eider Africa, TCC Africa, AfricArXiv, PREreview, and eLife are partnering to develop resources and a dissemination strategy for the delivery of an open peer review workshop to African research communities in the life sciences. Our goal is to build capacity and enthusiasm for scholarly open review of preprints among African researchers, and to provide opportunities to actively participate in peer review and gain recognition through community engagement. We will showcase our approach to co-creating resources and a replicable framework tailored to the needs and objectives of a growing community of African reviewers in the context of the changing global landscape of scientific research assessment and dissemination.
Keywords: Peer Review; Research in Africa; Multilingualism